ANDROID-BASED DISTRICT E-GOVERNMENT APPLICATION MODEL UI/UX PROTOTYPE USING DESIGN THINKING METHOD - Karmilasari, Ulva; -, Kurniawan (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2023)
The positive impact of rapid technological developments is widely felt in various aspects of human life. One example is improving the quality of public services at sub-district offices through the use of appropriate technology. E-Government is a new development in an effort to improve information and communication technology-based public services. This aims to make public services more transparent, accountable, effective and efficient. The E-Government application in this sub-district office requires a UI/UX design prototype model to help ease users in accessing the application. This study aims to design a UI/UX design prototype model in the sub-district office using design thinking. Researchers will analyze the problems faced by sub-districts in providing e-government services to the community, and develop a prototyping model of e-government applications that can provide a solution to the problem. The design thinking method will be used in the development of the prototype model. The Design Thinking method is an innovation-based software product design method that is based on finding solutions to solve certain problems. After successfully finding and understanding the problems found. The results of this report will later display a prototype in the form of an e-government website design that has been made. The Design Thinking method is an innovation-based software product design method that is based on finding solutions to solve certain problems. After successfully finding and understanding the problems found. The results of this report will later display a prototype in the form of an e-government website design that has been made. The Design Thinking method is an innovation-based software product design method that is based on finding solutions to solve certain problems. After successfully finding and understanding the problems found. The results of this report will later display a prototype in the form of an e-government website design that has been made.